Menguatkan Karakter Religius dan Toleran Anak Usia Dini Melalui Nilai-Nilai Islam dalam Cerita Rakyat Nusantara - Thowilah, Toyyibatut (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The development of religious and tolerant character from an early age is a strategic effort to instill Islamic values that are contextually and globally relevant. This study aims to explore the potential of Indonesian folktales as a medium for the internalization of Islamic values in strengthening the character of early childhood learners. The object of this study is the narrative content of selected folktales that reflect Islamic teachings and their implications for character education. The research method employed is library research with a content analysis approach applied to various literary sources, including traditional Indonesian folktales and relevant Islamic educational literature. The findings indicate that folktales such as Malin Kundang, Si Kabayan, and Lutung Kasarung convey moral messages that align with Islamic values, including obedience to parents, honesty, compassion, and tolerance. The novelty of this research lies in its integration of local wisdom and Islamic values within the framework of early childhood character education an area that remains underexplored in existing literature-based approaches. This distinguishes the study from prior research which tends to focus solely on general moral aspects without specific reference to Islamic teachings. The study concludes that folktales serve as an effective educational medium to harmonize local and global values in shaping a religious and tolerant character in young children.